Awareness as Correlate of Undergraduate Students’ Utilisation of Library Software in Universities in South-West, Nigeria - Oluwole Akanmu, Odunola; Adeyinka, Tella; Solomon Olusegun, Oyetola (International Journal of Knowledge Content Development & Technology, 2024)
This study investigated the awareness and utilisation of library software by undergraduate students in universities in South-west Nigeria. The descriptive research design of the ex post facto was adopted using a sample of 1,527 selected from the total population of 239,048 undergraduate students in the universities. A questionnaire was used to collect the data. The finding of the study revealed that the extent of utilisation of library software by undergraduate students was high. Also, the majority of undergraduate students utilised library software in the university libraries between two to three times a week. Similarly, the findings show that awareness had an influence on the utilisation of library software by undergraduate students in the universities (r = 0.563, N = 1333, P < 0.05). The study concluded that awareness influenced the utilisation of library software by undergraduate students in universities. The study, therefore, recommends that the importance of the awareness of library software should be emphasized in the library to enhance its utilisation by the students in the university libraries.